Psychology is social: Exploring universals in performance capacity and performance style - Fathali M. Moghaddam (Revista de Psicología, 2007)
Our goal in this discussion is to map out a scientifically legitimate and practical path toward internationalizing the social psychology curriculum. Toward developing an appropriate con- ceptual framework, we distinguish between the study of two different types of performance: performance capacity, how well isolated individuals can perform tasks as determined by their physical characteristics, and performance style, the way things are done through collab- orative meaning making. Whereas performance capacity can be explained causally, perfor- mance style is best explained through normative accounts. Social psychology has largely ap- proached questions of performance style by applying a reductionist and causal framework. We highlight the alternative approach reflected in the cultural-narrative turn and identify sub-research areas that need to be strengthened in order to internationalize psychology.